2022
DOI: 10.1002/ijc.34306
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of overall and early‐onset serrated polyps versus conventional adenomas in a colonoscopy screening cohort

Abstract: Serrated polyps (SPs) are precursors to one‐third of colorectal cancers (CRCs), with histological subtypes: hyperplastic polyps (HPs), sessile serrated lesions (SSLs) and traditional serrated adenomas (TSAs). The incidence of early‐onset CRC before the age of 50 is increasing, with limited understanding of SPs in younger cohorts. Using a large colonoscopy‐based cohort, we characterized epidemiologic profiles of SP subtypes, compared to conventional adenomas, with secondary analysis on early‐onset polyps. Ninet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…For endoscopic presentation, our results are generally consistent with previous studies ( 3 , 26 ). We found that compared to CAs, SSLs tended to be larger, predominantly located in the proximal colon, mostly as single lesions, mainly with a flat morphology.…”
Section: Discussionsupporting
confidence: 92%
“…For endoscopic presentation, our results are generally consistent with previous studies ( 3 , 26 ). We found that compared to CAs, SSLs tended to be larger, predominantly located in the proximal colon, mostly as single lesions, mainly with a flat morphology.…”
Section: Discussionsupporting
confidence: 92%
“…Tomonori Aoki 1 Yoku Hayakawa 1 Ryota Niikura 1,2 Nobumi Suzuki 1 Mitsuhiro Fujishiro 1 1 Department of Gastroenterology, Graduate School of Medicine, the University of Tokyo, Tokyo, Japan 2…”
Section: Funding Informationmentioning
confidence: 99%
“…
We read the recent publication written by Vithayathil et al 1 with great interest, wherein the authors have conducted a large colonoscopybased cohort study to evaluate epidemiologic profiles of the sessile serrated lesions (SSLs), compared them with conventional adenomas, and performed secondary analysis on early-onset polyps. The prevalence of
…”
mentioning
confidence: 99%
“…While microvesicular HPs and SSLs occur more commonly in the left and right colon respectively, both lesions can occur anywhere within the large intestine, and therefore, a specific diagnosis of serrated lesion type is not dependent on its anatomical location 1. For example, a study of over 94 000 screening colonoscopies found the following patterns of distribution of HPs and SSLs in individuals aged over 50 years: HP—proximal colon 26.6%, distal colon 51.5%; rectum 38.6%; SSL—proximal colon 84.4%, distal colon 15.2%, rectum 4.4%) 8…”
Section: Introductionmentioning
confidence: 99%